2017
DOI: 10.24200/sci.2017.4291
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension simulation of free surface flows using smoothed particle hydrodynamics

Abstract: Abstract. SPH method is one of the most used numerical mesh-free methods in CFD simulations which can easily model problems with free surfaces. Considering the importance of surface tension in most engineering applications and the capability of SPH method in simulating free surfaces, a single-phase method for implementing surface tension is introduced in this study. Unlike time-consuming multi-phase simulations, this method does not need to model the second lighter uid, which reduces the CPU-time and memory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…(2.11) requires the whole domain to be filled with SPH particles, hence it is not suitable for multiphase computations in which the lighter phase is neglected, e.g. see the approach proposed by Ordoubadi et al (2017).…”
Section: Governing Equationsmentioning
confidence: 99%
“…(2.11) requires the whole domain to be filled with SPH particles, hence it is not suitable for multiphase computations in which the lighter phase is neglected, e.g. see the approach proposed by Ordoubadi et al (2017).…”
Section: Governing Equationsmentioning
confidence: 99%
“…This kernel truncation error at the free surface in CSF has been addressed using several strategies. Mirror particles were employed by Ordoubadi, Yaghoubi & Yeganehdoust (2017) to produce robust two-dimensional flow simulations in weakly compressible SPH. Hirschler et al (2017) used CSF to simulate two-dimensional droplet collisions at the free surface using kernel correction parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Huber et al [ 11 ] introduced a balance equation for the contact line between the two fluid phases and the substrate to accurately model advancing and receding contact angles in dynamic wetting situations. Ordoubadi et al [ 12 ] used a single-phase SPH formulation for the CSF approach in which they identified the surface by a combination of a geometric interface tracking and the calculation of the position divergence field [ 13 ]. Hirschler et al [ 14 ] formulated a single-phase model which obtains the surface normal and the surface delta function directly from the SPH kernel gradient.…”
Section: Introductionmentioning
confidence: 99%